ANALISIS FISH BURGER DENGAN PENAMBAHAN SURIMI IKAN TUNA (THUNNUS, SP) DENGAN KOMPOSISI TEPUNG ROTI YANG BERBEDA - Dahlan Amura; Nur Asyah Saimima; Desri N Manuhutu; Sudaryo Ura (Journal of Aceh Aquatic Sciences, 2021)
This study aims to determine the effect of adding bread flour to water content, ash content, protein content, fat content and carbohydrate content of tuna burgers. This study used a completely randomized design (CRD) with 5 treatments, each of which was repeated 3 times. The treatment levels of this study are as follows: giving different concentrations of bread flour, namely 90%, 85%, 80%, 75% and 70%, respectively. The addition of surimi treatment for tuna and bread flour had a very significant effect on chemical parameters, namely water content, protein content, fat content, carbohydrate content and had no significant effect on ash content. The best treatment composition was found in the B4 chemical test, namely: 39.59% water content, ash content 2.71%, protein content 13.72% 19.20% fat content and 19.51% carbohydrate content.